Indonesian as a Regional Lingua Franca in the Asean Economic Community - Fahmy Lukman; Riki Nasrullah; Cece Sobarna; Tubagus Chaeru Nugraha; Muhammad Zulfi Abdul Malik; El-Sawi Ahmed Abdel Rahim (Jurnal Ilmiah Peuradeun, 2026)
Despite sustained policy initiatives to promote Bahasa Indonesia internationally, its strategic development as a regional lingua franca within the ASEAN Economic Community has received limited scholarly attention, particularly in relation to economic integration and multilingual governance. This study examines whether Indonesian can function as a regional lingua franca in ASEAN and analyses how its internal linguistic conditions (strengths and weaknesses) and external environment (opportunities and threats) shape its internationalization prospects. Employing a qualitative research design, the study applies a structured SWOT analysis to official policy documents, institutional strategies, and regional cooperation frameworks relevant to ASEAN. The findings reveal that, despite strong demographic presence, legal recognition, and geopolitical significance, the internationalization of Indonesian is constrained by fragmented governance, limited cross-sectoral coordination, and the absence of a coherent long-term strategic roadmap. The study argues that advancing Indonesian as a regional lingua franca requires a paradigmatic shift in language policy, reconceptualizing it as a multi-sectoral process integrated with diplomacy, economic cooperation, education, and cultural governance. Rather than serving solely as a communicative medium, Indonesian must be positioned as a strategic policy asset embedded within ASEAN’s political–economic structures. By situating Indonesian within a Global South perspective, this study contributes to broader debates on regional lingua franca formation beyond English-centred models.